Application of the Steam Approach in Efforts to Improve 4c Skills in Elementary School Students - Ironysa Inez Fitria; Feny Rita Fiantika; Susi Hermin Rusminati (Formosa Journal of Sustainable Research, 2023)
This research is motivated by the need for renewal in the learning process and the importance of students having 4C skills in the 21st century. The purpose of this research is to describe the application of the STEAM approach to improve 4c skills. This research uses a descriptive qualitative approach. The data collection techniques used are observation, tests, questionnaires and documentation. The result of this research learning process is that the STEAM approach is effectively used. High category students understand the material and get perfect scores. Medium category students are able to understand the material with few errors, and the location of the error is understanding the nature of spatial shapes. Meanwhile, low category students have not been able to understand the material with many errors, and the errors is in understanding the nature of spatial shapes and how to draw shapes that do not match the achievement indicators